2013
DOI: 10.3390/molecules18032967
|View full text |Cite
|
Sign up to set email alerts
|

Rare Syringyl Acylated Flavonol Glycosides from the Aerial Parts of Leonurus japonicus Houtt.

Abstract: Abstract:Five new syringyl acylated flavonol glycosides, named leonurusoides A (1), B (2), C (3), D (4), and E (5), together with one known one 6 were obtained from the aerial parts of Leonurus japonicus. Their structures were elucidated by chemical and spectroscopic methods (UV, IR, HRESI-TOF-MS, 1D and 2D NMR). Compounds 16 showed triglyceride (TG) accumulation inhibitory effects in free fatty acid-induced HepG2 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…Our results demonstrated that LJE treatment significantly inhibited lipid accumulation and intracellular TG levels in a concentration-dependent manner in FFA-treated HepG2 cells. Consistent with these findings, a previous study stated that leonurusoides from the aerial parts of L. japonicus inhibited TG accumulation in HepG2 cells treated with 0.2 mM oleic acid [ 20 ].…”
Section: Discussionsupporting
confidence: 80%
“…Our results demonstrated that LJE treatment significantly inhibited lipid accumulation and intracellular TG levels in a concentration-dependent manner in FFA-treated HepG2 cells. Consistent with these findings, a previous study stated that leonurusoides from the aerial parts of L. japonicus inhibited TG accumulation in HepG2 cells treated with 0.2 mM oleic acid [ 20 ].…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, plasma cholesterol decreased and high density lipoproteincholesterol increased has been reported in L. sibiricus herb extract supplemented feed in mice (Lee et al,2010). Triglyceride (TG) accumulation inhibitory effects has been reported in free fatty acid-induced HepG2 cells due to flavonoids leonurusoides (Zhang et al, 2013) in HW. Our current findings is more or less similar to buckwheat and black cumin supplemented feed .…”
Section: Discussionmentioning
confidence: 99%
“…The dried herb is used in TCM for the treatment of various diseases, such as menstrual disturbances, dysmenorrhea, and amenorrhea (Liu et al, 2014). Recently, phytochemical studies on this plant have been reported (Romero-González et al, 2006;Ye et al, 2014;Fuchino et al, 2013;Chang et al, 2010;Moon, 2010;Xiong et al, 2013a,b;Zhang et al, 2013;Peng et al, 2013). Our previous investigation on two plants of the family of Lamiaceae resulted in the isolation of a number of new labdane diterpenes (Wu et al, 2011.…”
Section: Introductionmentioning
confidence: 95%